Mobile Technology Facilitated Physics Learning Course: A Systematic Review from 2010 to 2019 (International Conference on Computers in Education, 2020)
This paper summarizes the research on the use of mobile technology over the last ten years, where mobile learning issue in physics education have been discussed. However, there is less study revealing the trend of applying mobile technologies for teaching/learning physics regarding systematic analysis. In this study, a meta review of the studies published in academic journals indexed by SCOPUS ranging from 2010 to 2019 was conducted to analyze years of published paper, and learning strategies. The results revealed that the use of mobile technologies in physics education have been increased in the past decade. It was also found that mostly mobile technologies have been applied in scientific experiment for physics learning as a learning tool. In addition, mobile learning strategies have seldom been adopted in inquiry learning, research and development, blended learning, collaborative and STEM. In contrast, it was found that the number of studies using a system development has been increasing in recent years.